A paradox of cumulative culture. (21st August 2015) - Kobayashi, Yutaka; Wakano, Joe Yuichiro; Ohtsuki, Hisashi
Abstract: Culture can grow cumulatively if socially learnt behaviors are improved by individual learning before being passed on to the next generation. Previous authors showed that this kind of learning strategy is unlikely to be evolutionarily stable in the presence of a trade-off between learning and reproduction. This is because culture is a public good that is freely exploited by any member of the population in their model (cultural social dilemma). In this paper, we investigate the effect of vertical transmission (transmission from parents to offspring), which decreases the publicness of culture, on the evolution of cumulative culture in both infinite and finite population models. In the infinite population model, we confirm that culture accumulates largely as long as transmission is purely vertical. It turns out, however, that introduction of even slight oblique transmission drastically reduces the equilibrium level of culture. Even more surprisingly, if the population size is finite, culture hardly accumulates even under purely vertical transmission. This occurs because stochastic extinction due to random genetic drift prevents a learning strategy from accumulating enough culture. Overall, our theoretical results suggest that introducing vertical transmission alone does not really help solve the cultural social dilemma problem. Highlights: Infinite and finite population models of gene-culture coevolution are considered. A social dilemma caused by the publicness of culture disfavors cumulative culture. Privatization of culture by vertical transmission is considered. Slight oblique transmission is enough to prevent cumulative cultural evolution. Genetic drift in a finite population prevents cumulative cultural evolution.